2012
DOI: 10.1007/s00380-011-0226-1
|View full text |Cite
|
Sign up to set email alerts
|

Hsp90 and its co-chaperone, Sgt1, as autoantigens in dilated cardiomyopathy

Abstract: Recently, it has been suggested that some heat shock proteins such as Hsp70 and Hsp60 are involved in autoimmune diseases including cardiospecific ones. In this work we focused on the involvement of another wellknown heat shock protein, Hsp90, and its novel co-chaperone,Sgt1, in dilated cardiomyopathy (DCM). We found that the level of autoantibodies against these two proteins was significantly higher in patients with DCM and ischemic heart disease than in sera of healthy donors. We have also analyzed the expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…As mentioned above, we have shown that Sgt1 interacts with Hsps (Hsp90 and Hsp70) through the C-terminal domain, which also binds S100A6, and that S100A6 competes for the binding [Nowotny et al, 2003;Spiechowicz et al, 2007] Our group has demonstrated that Sgt1 exhibits cochaperone properties and may also act as a chaperone itself since it is able to protect proteins from thermal aggregation as shown by the citrate synthase assay [Żabka et al, 2008]. Furthermore, we have shown for the first time that the level of Sgt1 increases due to stress conditions [Żabka et al, 2008;Kapustian et al, 2013] similarily to the level of Hsps. In the case of heat shock, the increase in Sgt1 level is caused by transcription stimulation of the Sgt1 gene by HSF-1 transcription factor that binds to the promoter.…”
Section: Involvement Of Sgt1 In Chaperone Complexes and Cell Prolifermentioning
confidence: 75%
“…As mentioned above, we have shown that Sgt1 interacts with Hsps (Hsp90 and Hsp70) through the C-terminal domain, which also binds S100A6, and that S100A6 competes for the binding [Nowotny et al, 2003;Spiechowicz et al, 2007] Our group has demonstrated that Sgt1 exhibits cochaperone properties and may also act as a chaperone itself since it is able to protect proteins from thermal aggregation as shown by the citrate synthase assay [Żabka et al, 2008]. Furthermore, we have shown for the first time that the level of Sgt1 increases due to stress conditions [Żabka et al, 2008;Kapustian et al, 2013] similarily to the level of Hsps. In the case of heat shock, the increase in Sgt1 level is caused by transcription stimulation of the Sgt1 gene by HSF-1 transcription factor that binds to the promoter.…”
Section: Involvement Of Sgt1 In Chaperone Complexes and Cell Prolifermentioning
confidence: 75%
“…The complete list of compounds ranked by FPAScores is available in Additional file 8 . The compounds include promising drug candidates, for example, two heat shock protein 90 (HSP90) inhibitors are upregulated in dilated cardiomyopathy [ 16 ], and two PPAR inhibitors are regarded as pharmacological therapeutic targets [ 17 ]. Furthermore, overexpression of two Cyclin-dependent kinase 2 (CDK2) inhibitors results in smaller mononuclear cardiomyocytes [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…For example, hypoxia and tnF alpha synergistically induce heat shock protein 90 (Hsp90) [29] which prevents cell apoptosis via PI3-K/akt activation [30]. Hsp90 was reported to increase in DcM patients [31].…”
Section: Discussionmentioning
confidence: 99%